ANALYSIS OF TECHNOLOGY ACCEPTANCE MODEL AT TIKTOK SHOP IN BEKASI CITY IN GEN Z AND MILENIALS - Putra, Hillary Pranata; Indika, Deru R (Jurnal Ekonomi Manajemen, 2023)
This study aims to analyze the Technology Acceptance Model at the Tiktok Shop in Bekasi City regarding the effect of perceived usefulness and perceived ease of use on consumer attitudes among Gen Z and Millennials. TikTok Shop, which is a social media platform as well as an e-commerce forum, brings changes to the e-commerce system through the uniqueness of the shopping activities in it. This uniqueness is something new for the community, so it is closely related to the TAM concept, which focuses on accepting new technology. The method used in this study uses both descriptive and verification methods. By collecting data through a survey by distributing questionnaires, which obtained 211 respondents from generation Z and millennials who are TikTok Shop users in Bekasi city. The data obtained were analyzed using the SEM PLS method. The results showed that there was a positive and significant effect of perceived usefulness on consumer attitudes; perceived ease of use had a positive and significant effect on consumer attitudes; perceived ease of use had a positive and significant effect on perceived usefulness; and perceived ease of use had a positive and significant effect on consumer attitudes through perceived usefulness.